Reducing global poverty the case for asset accumulation - Moser, Caroline O. N. (Brookings Institution Press, 2007)
"Provides a set of case studies of asset-building projects around the globe aimed at designing and implementing public policies that will increase the capital assets of the poor. Highlights the ways in which poor households and communities can move out of poverty through longer-term accumulation of capital assets"--Provided by publisher.